FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG - Eri Valinsia Wijaya; Mungniyati (E-Jurnal Akuntansi TSM, 2022)
This research aims to empirically prove the effect of Company Size, Profitability, Solvability, Age of Company, Accounting Firm Size, Auditor Opinion, Auditor Switching, Complexity, and Board of Size of Director. This research uses manufacturing companies that consistently listed on Indonesia Stock Exchange during the period 2018 to 2020 as the population. The sample was obtained by using purposive sampling method and obtained a total sample of 72 manufacturing companies that listed on Indonesia Stock Exchange during the period 2018 to 2020 that meet the sampling criteria. The result of this research show that Solvability and Accounting Firm Size have a negative effect on Audit Report Lag. Meanwhile, Company Size, Profitability, Age of Company, Auditor Opinion, Auditor Switching, Complexity, and Board of Size of Director have no effect on Audit Report Lag.